Sarcopenia in cirrhosis of liver - comparison of different tools in diagnosis - Pathak, Rahul; Lamsal, Manoj; Jha, Ashis Kumar; Sherpa, Tshering Wangdi; Hamal, Rabin (Journal of Advances in Internal Medicine, 2024)
BACKGROUND AND AIMS Sarcopenia in liver cirrhosis is a common condition associated with increased mortality and adverse clinical outcome. Early recognition and treatment is essential but challenging. Clinical detection of sarcopenia with various assessment tools gives indirect knowledge of muscle mass and strength. The aim of this study is to find the most easy and applicable assessment tool in daily clinical practice to diagnose sarcopenia. METHODS A retrospective observational study was conducted and data was taken from electronic medical records of patients admitted with cirrhosis and sarcopenia in department of gastroenterology of Tribhuvan university Teaching hospital. A total of 51 cirrhotic patients were included during one and half year study duration. Sarcopenia was assessed using assessment tool like hand grip strength, chair stand test, 400 metre walk test and CT measurement of either skeletal muscle area (SMA) or skeletal muscle index (SMI). RESULTS Among 51 patients assessed with performance based assessment tool to diagnose sarcopenia, taking CT as gold standard test, SARC-F score and chair stand test were found to have highest sensitivity and specificity of 93%, 87.5 % and 93%, 100% respectively. CONCLUSION Diagnosis of sarcopenia with simple clinic based assessment tool SARC-F score and chair stand test is very useful and comparable with more costly and resource-intensive CT scan.